ANALYSIS OF THE NUTRITIONAL ASSESSMENT OF WORKERS IN THE GAS-CHEMICAL INDUSTRY - Sabirova G.A., (Central Asian Journal of Medicine, 2025)
This study presents an analysis of the nutritional assessment of workers in the gas-chemical industry, focusing on dietary habits, nutritional status, and potential health risks associated with occupational exposure. The research highlights the importance of proper nutrition in maintaining workers' health and productivity, particularly in high-risk industrial environments. By evaluating the dietary intake and comparing it with established nutritional norms, the study identifies common deficiencies and imbalances that may contribute to occupational health problems. Recommendations are provided to improve dietary practices and promote better health outcomes among industry workers.